دور خدمات وكالات الصرافة في دعم الاستقرار المالي من وجهة نظر العملاء دراسة واقع خدمات مكاتب الصرافة في الجنوب الغربي الليبي (وادي الآجال) (Comprehensive Journal of Science, 2026)
This study aimed to identify the role of exchange agencies in supporting financial stability from the perspective of their customers. The study adopted the descriptive-analytical approach and utilized a questionnaire distributed to a sample of (53) customers of exchange agencies. Data were analyzed using the Statistical Package for the Social Sciences (SPSS), employing both descriptive and inferential statistical methods, including means, correlation coefficient analysis, and regression analysis.The results revealed a statistically significant moderate relationship between exchange agency services and their dimensions and financial stability, estimated at (69%). The hypothesis testing results rejected the first, second, and third null hypotheses, which assumed that there was no effect of exchange agency services in terms of (accessibility and service availability, service quality and speed of processing, transparency and fairness in pricing and fees) on financial stability. Conversely, the fourth hypothesis was accepted, confirming a statistically significant effect of exchange agency services in terms of (trust, security, and customer protection) on financial stability.Furthermore, the findings indicated that exchange agency services explain approximately 48% of the variations occurring in financial stability. This suggests that exchange agencies represent one of the main determinants of enhancing financial stability and constitute an effective financial channel that facilitates daily cash transactions, reduces pressure on banks, and supports overall financial stability.In light of these findings, the study recommends improving service quality and transaction processing speed, enhancing employees’ interaction with customers, expanding agency presence in areas with limited banking services, strengthening regulatory oversight to ensure unified pricing standards and transparency, and obligating agencies to clearly disclose exchange rates and fees.
Keywords: Exchange Agencies; Financial Stability; Exchange Offices; Foreign Exchange Market.